THE EFFORT ANALYSIS OF STUDENT’S CRITICAL THINKING SKILLS PROGRAM IMPROVEMENT USING A GUIDED INQUIRY APPROACH BASED ON BLENDED LEARNING - Akhmad Ramli; Wa Ode Riniati; Gamar Al Haddar; Haris Munandar; Ahmad Zulfahmi Ubaidillah (Sean Institute, 2023)
Pupils' poor critical thinking abilities in the static fluid notion are the result of a learning procedure that does not actively engage pupils and does not develop their critical thinking abilities. This study tries to ascertain how students' critical thinking abilities are affected by the guided inquiry approach that is based on blended learning. In this study, 40 students from the experimental class and 40 from the control class made up the sample. study was conducted using a non-equivalent-control group study design and a quasi-experiment method. Using a critical thinking instrument with 10 questions, students' critical thinking abilities are evaluated. A sig value < 0.05 was calculated from the Mann-Whitney test results on the posttest data. This leads to the conclusion that Ha is accepted, which indicates that the guided inquiry model based on blended learning has an impact on students' critical thinking abilities. The N-Gain data demonstrate that the experimental class increased more than the control class did. 80% of student responses to the guided inquiry model based on blended learning fell into the very good category.